New analytical method for dynamic response of thermoelastic damping in simply supported generalized piezothermoelastic nanobeam. Issue 10 (8th May 2021) - Kaur, Iqbal; Singh, Kulvinder; Ghita, Gilbert Marius Daniel
Abstract: The present paper deals with the application of one‐dimensional piezoelectric materials in particular piezo‐thermo‐elastic nanobeam in the context of generalized piezothermoelastic theory. The ends of the nanobeam are considered to be simply supported and at a constant temperature. The mathematical model so formed is solved to obtain the non‐dimensional expressions for lateral deflection, electric potential, thermal moment, thermoelastic damping, and frequency shift. Effect of frequency on the lateral deflection, electric potential, thermal moment with generalized piezothermoelastic theory are represented graphically using the MATLAB software. Comparisons are made with different theories of thermoelasticity. Abstract : The present paper deals with the application of one‐dimensional piezoelectric materials in particular piezo‐thermo‐elastic nanobeam in the context of generalized piezothermoelastic theory. The ends of the nanobeam are considered to be simply supported and at a constant temperature. The mathematical model so formed is solved to obtain the non‐dimensional expressions for lateral deflection, electric potential, thermal moment, thermoelastic damping, and frequency shift.…